2010
DOI: 10.1007/s10267-010-0053-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Armillaria species associated with Polyporus umbellatus using ITS sequences of nuclear ribosomal DNA

Abstract: The sclerotia of Polyporus umbellatus were collected from three locations in Japan and three locations in China. All the collected sclerotia were adhered to by rhizomorphs of the symbionts. When the sclerotium of P. umbellatus was cross sectioned, the internal part of the sclerotium was cream colored, and many black regions surrounding the invading rhizomorphs were observed. The surrounding zone contained string-like, gelatinous masses composed of hyphae, and its outside was brown in color. All isolates were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…The dendrogram tree of 8 natural Polyporus umbellatus strains collected from 7 provinces in China based on Jaccard similarity coefficients by using unweighted pair group method with arithmetic mean method from sequence-related amplified polymorphism markers. The numbers correspond to those listed in Table 1. several biological species in North America, Europe, Australia, Japan, and China (Kikuchi and Yamaji, 2010;Wang, 2010). Moreover, chuling associates with many Armillaria species in China and Japan (Kikuchi and Yamaji, 2010), although Xu et al (2003) have reported that Armillaria mellea can form the sclerotium of chuling.…”
Section: Genetic Diversity and Genetic Variation Among Chuling Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dendrogram tree of 8 natural Polyporus umbellatus strains collected from 7 provinces in China based on Jaccard similarity coefficients by using unweighted pair group method with arithmetic mean method from sequence-related amplified polymorphism markers. The numbers correspond to those listed in Table 1. several biological species in North America, Europe, Australia, Japan, and China (Kikuchi and Yamaji, 2010;Wang, 2010). Moreover, chuling associates with many Armillaria species in China and Japan (Kikuchi and Yamaji, 2010), although Xu et al (2003) have reported that Armillaria mellea can form the sclerotium of chuling.…”
Section: Genetic Diversity and Genetic Variation Among Chuling Strainsmentioning
confidence: 99%
“…The numbers correspond to those listed in Table 1. several biological species in North America, Europe, Australia, Japan, and China (Kikuchi and Yamaji, 2010;Wang, 2010). Moreover, chuling associates with many Armillaria species in China and Japan (Kikuchi and Yamaji, 2010), although Xu et al (2003) have reported that Armillaria mellea can form the sclerotium of chuling. Therefore, different environments may affect the composition of Armillaria species populations, which would form selection pressure on the genetic structure of local chuling strains.…”
Section: Genetic Diversity and Genetic Variation Among Chuling Strainsmentioning
confidence: 99%
“…Normal mycelia can turn into sclerotia as a hardened mass of mycelia under environmental extremes of cold, drought and nutritional depletion (Liu and Guo 2010). Guo and Xu (1992) elucidated that, in wild conditions, sclerotia of P. umbellatus cannot grow or produce new sclerotia without Armillaria mellea, which has a strong and special symbiotic relationship with P. umbellatus Xu 1992, 1993;Xu et al 2003;Kikuchi and Yamaji 2010). A. mellea can provide sclerotia of P. umbellatus with nutrients after the subtle symbiosis between the two fungi has formed (Guo and Xu 1991).…”
Section: Introductionmentioning
confidence: 97%
“…Attempts have been made to identify the Armillaria species that are associated with P. umbellatus in Japan (Kikuchi and Yamaji, 2010). To date, very limited information is available on phylogenetic relationship and genetic diversity in Armillaria species associated with P. umbellatus around China.…”
Section: Introductionmentioning
confidence: 99%
“…Fries belongs to a genus of Polyporaceae and, has been considered to be a species of woodrotting fungi (Kikuchi and Yamaji, 2010). P. umbellatus sclerotia is widely distributed in both broad-leaved and coniferous forests in Asia, Europe and temperate regions of the Northern Hemisphere (Zhao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%